Wittichenite semiconductor of Cu3BiS3 films for efficient hydrogen evolution from solar driven photoelectrochemical water splitting - Dingwang Huang (Nature Portfolio, 2021)
A highly efficient, stable, low-cost and environmentally friendly photocathode is the goal of practical solar hydrogen evolution applications. Here, authors report a Cu3BiS3-based photocathode and Cu3BiS3-BiVO4 tandem cell for unbiased overall solar water splitting with a STH efficiency over 2%.